Market Expansion Strategies for Turfgrass Producers in the Western United States - John J. Haydu; Alan W. Hodges; Loretta N. Satterthwaite (EDIS)
This paper reports the results of the third and last phase of a turfgrass marketing study in the United States. The previous two phases of this study were conducted in the Eastern and Central United States. This research project was a joint effort by International Turfgrass Producers Foundation (ITPF) and the University of Florida’s Institute of Food & Agricultural Sciences. Revised February 26, 2003.